Evaluation of imaging by radiography, ultrasonography and computed tomography in suspected cases of intestinal obstruction and its comparison with operative findings - Babu, Nyla Mary; Varghese V., Binoj; Kavalakat, Alfie J.; Mathew, James; George, Divya Acma; Mathew, Jubin (International Journal Of Community Medicine And Public Health, 2025)
Background: Intestinal obstruction is a common surgical emergency, accounting for up to 20% of acute abdominal surgeries. Rapid diagnosis is essential to prevent complications like ischemia, gangrene, and perforation. Imaging modalities play a critical role in identifying the site, cause, and severity of obstruction. The objectives of the study were to evaluate and compare the diagnostic accuracy of abdominal radiography, ultrasonography (USG), and computed tomography (CT) in detecting intestinal obstruction and its cause with intraoperative findings. Methods: This prospective diagnostic evaluation study was conducted over 10 months in the department of radiodiagnosis at a private medical college in Thrissur. A total of 40 adult patients clinically suspected of intestinal obstruction who underwent radiograph, USG, CT, and subsequent surgery were included. Imaging findings were compared with intraoperative diagnoses. Statistical analysis was done using Chi-square and Fisher’s exact tests. Results: Among 40 participants, 82.5% were over 40 years and 57.5% were males. CT showed the highest sensitivity (100%) and NPV (100%) in detecting the cause of obstruction, while USG had good sensitivity (72.7%) and specificity (88.9%). Radiography showed low sensitivity (0%) but high specificity (100%). CT identified transition points in 95% of cases and the underlying cause in 70%, outperforming USG and radiography. Intraoperatively, adhesions (45%) and lesions (55%) were the common etiologies. Conclusions: CT is the most accurate modality for diagnosing intestinal obstruction. While radiography remains useful for initial assessment, combining it with USG and CT improves diagnostic accuracy and guides timely surgical intervention.